Supplementary data for: Chromosome-level genome assembly and circadian gene repertoire of the Patagonia blennie Eleginops maclovinus ... - Rivera-Colón, Angel (Dryad, 2023)
This dataset contains the genome assembly and associated annotation of the Patagonian Blennie (Eleginops maclovinus), the closest extant taxon to the Antarctic notothenioid radiation. In addition to the characterization of the E. maclovinus genome, the dataset includes a description of circadian rhythm orthologs for E. maclovinus, other notothenenioid taxa, and teleost outgroups, as well as a copy of the bioinformatic scripts used for the assembly, annotation, and other downstream analysis. ... : An E. maclovinus specimen was collected from the Puerto Natales, Chile in January 2018. HMW DNA was extracted and sequenced using PacBio Sequel II and a Hi-C library. A contig-level genome assembly was first generated using wtdgb2 (a.k.a. redbean) v2.5 (Ruan & Li 2020), and scaffolded with juicer v1.6.2 (Durand et al. 2016). PacBio and HiC raw data is available under NCBI BioProject PRJNA857989. For annotation, the RNA-seq data generated by Bilyk et al. (2018) was aligned to the genome, and processed using BRAKER v2.1.6 (Brůna et al. 2021). The generated annotation was then further processed using TSEBRA v1.0.1 (Gabriel et al. 2021). Using a custom Python script (see scripts section), we curated the TSEBRA output to guarantee consistency in the naming of genes and transcripts, as well as incorporating gene names and description based on the corresponding zebrafish orthologs. A conserved synteny analysis using synolog (Catchen et al. 2009; Small et al. 2016) was employed for the manual curation of the ...